2006
DOI: 10.1080/15017410500335229
|View full text |Cite
|
Sign up to set email alerts
|

Community Receptivity: The Ecology of Disabled Persons’ Participation in the Physical, Political and Social Environments

Abstract: The physical environment is the space in which people with a disability participate in the public sphere. The community provides a suitable unit of analysis for investigating the interaction between the physical environment and persons with a disability because it is the common space in which public participation is played out. The places, physical features, structures and objects that constitute the physical environment bear the inscription of the social, political and economic environments. The physical envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 49 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Previous studies revealed that there is a relationship between participation and environmental factors at all levels, including features of the natural and built world, as well as attitudes of others and social policies that affect people with disabilities [2,[13][14][15][16][17]. By using structural equation modeling, Hollingsworth and Gray [16] found a moderately strong relation between the environment and activity participation for those with mobility impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that there is a relationship between participation and environmental factors at all levels, including features of the natural and built world, as well as attitudes of others and social policies that affect people with disabilities [2,[13][14][15][16][17]. By using structural equation modeling, Hollingsworth and Gray [16] found a moderately strong relation between the environment and activity participation for those with mobility impairments.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, use of community life space reflects the potential for community participation. This dichotomization from home to community spaces is critical as increasingly accessing community spaces provides and enhances opportunities for continued participation in societal roles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[17] Examples of factors influencing conversations are noise and the arrangement of furniture. [17] Since the physical environment and other ICF environmental factors (support and relationships, attitudes, and services, systems and policies) have a reciprocal relationship, [18] more knowledge is needed about the impact of the physical environment in order for professionals and health-care systems to create communication friendly environments. Adapting or modifying existing physical environments, and designing new environments that promote universal communication access, is important.…”
Section: Introductionmentioning
confidence: 99%